Schwinger's principle and gauge fixing in the free electromagnetic field - De Melo, C. A M [UNESP]; Pimentel, B. M. [UNESP]; Pompeia, P. J. [UNESP] (My University, 2006)
A manifestly covariant treatment of the free quantum eletromagnetic field, in a linear covariant gauge, is implemented employing Schwinger's variational principle and the B-field formalism. It is also discussed the Abelian Proca model as an example of a system without constraints. © Società Italiana di Fisica.